2015
DOI: 10.1093/bja/aev221
|View full text |Cite
|
Sign up to set email alerts
|

Strong ion and weak acid analysis in severe preeclampsia: potential clinical significance

Abstract: clinicaltrials.gov: NCT 02164370.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
5
0
2
Order By: Relevance
“…Stewarts approach has also been adopted for greater understanding of preeclampsia. One study performed acid-base analysis by the Stewart-Gilfix approach in healthy pregnant women and women with preeclampsia (90). A conventional analysis would not have revealed any dissimilarities as base excess was similar in both groups, but the difference in metabolic components became apparent when adopting the Stewart-Gilfix approach.…”
Section: Interpretation According To Stewart Of Pregnancy Induced Chamentioning
confidence: 99%
See 1 more Smart Citation
“…Stewarts approach has also been adopted for greater understanding of preeclampsia. One study performed acid-base analysis by the Stewart-Gilfix approach in healthy pregnant women and women with preeclampsia (90). A conventional analysis would not have revealed any dissimilarities as base excess was similar in both groups, but the difference in metabolic components became apparent when adopting the Stewart-Gilfix approach.…”
Section: Interpretation According To Stewart Of Pregnancy Induced Chamentioning
confidence: 99%
“…The application of Stewart´s principles also to analysis of physiological changes of pregnancy would increase understanding and acceptance when Stewart´s principles are applied to study pathological conditions. One recent study showed how analysis according to Stewart-Gilfix could offer predictive information in preeclamptic women (90).…”
Section: Paper 4 Feto-maternal Osmotic Relationshipmentioning
confidence: 99%
“…The presence of a significant metabolic alkalosis did not seem to overtly endanger the life of the patient as the mortality rates were similar in each group though, once again, the study numbers were relatively small. Finally, a low serum albumin, a common finding in critically ill patients, also contributed to the resultant acidbase disturbance by worsening any metabolic alkalosis [12][13][14] .…”
Section: Primary End Pointmentioning
confidence: 99%
“…El exceso o déficit de bases (EDB) se define como la cantidad de ácido o base fuerte necesaria para que el pH retorne a un valor de 7,4 a un valor de presión parcial de CO 2 en sangre arterial de 40 mmHg y a 37 °C de temperatura (14,15). Es más sensible para identificar hipoperfusión que el pH y el bicarbonato, sobre todo en pacientes de trauma, donde cuenta con más estudios.…”
Section: Introductionunclassified